Diagnosis and treatment of intravesical obstruction as a complication after TVT surgery for the treatment of stress urinary incontinence in women - Georgi, Hubchev (International Journal of Psychosocial Rehabilitation, 2020)
The focus of the publication is the diagnosis and treatment of intravesical obstruction - a complication after TVT surgery. The aim is to establish the complication rate. For the period 2005-2019. 436 women with TVT were operated on for treatment of stress incontinence, 45 (10.3%) of them developed IVO. In 334 women using the TVT-O-33 method, IVO was developed, in 78 operated on TVT-R, the problem was in 12 patients, and in 24 with TVT-Ophira, this complication was not detected. Early IVO at day 1 postoperatively was observed in 16 women (35.5%), at day 14 IVO had 53.3%, and late complication was observed in 5 patients (11.1%). Treatment begins with conservative methods, and in the case of non-response proceeds to surgery. I used a retrospective method to determine the complication rate within the appropriate postoperative period. The study concluded that 15.4% of IVO was detected after TVT-R, 9.8% with TVT-O and 0% with Single incision.